Peran Kepemimpinan Kepala Madrasah dalam Membangun Budaya Belajar yang Efektif di Lingkungan Pendidikan MTs Darul Aitam Jerowaru: The Role of Madrasah Principal Leadership in Building an Effective Learning Culture in the Educational Environment of MTs Darul Aitam Jerowaru - Abdurrahim; Kamaruddin; Jamaludin; Ade Mariana Ayu; Lisnaini (Pendidikan Al-Gafari, 2026)
This study aims to describe the leadership role of the madrasah principal in building an effective learning culture, identifying the strategies implemented, and knowing the indicators of success. The approach used in this study is a qualitative approach with a case study method. Data collection techniques include in-depth interviews, participant observation, and documentation. The results of the study indicate that: (1) The madrasah principal has a central role in forming an effective learning culture, which is reflected through active involvement in the learning process by adopting the principles of transformational and instructional leadership, which emphasize influence, motivation, and direct participation in learning activities. (2) The strategies implemented in creating a conducive learning environment include supervision and mentoring of teachers, as well as strengthening communication, providing motivation. (3) Indicators of the success of an effective learning culture at MTs Darul Aitam Jerowaru can be seen from the increase in student discipline, active participation in the learning process.